Nilai-nilai pendidikan karakter dalam upacara Rambu solo’ di Tana Toraja - Serdianus Serdianus (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This research aims to identify character education values in Torajan culture, particularly through the analysis of rambu solo' (death ceremony). The method used is library research with a qualitative approach. The results showed that the rambu solo' ceremony contains important values such as mutual cooperation, helping each other, and religious values about life after death. Rambu solo' has a central role in shaping the character education ideals of the Toraja people, reflecting the cultural wealth passed down through generations. Values such as togetherness, persistence and family ties are seen in the implementation of rambu solo'. Despite conflicts with Christian teachings, this research highlights the importance of understanding and respecting cultural heritage, while seeking ways to integrate Torajan cultural values with Christian beliefs. This research contributes to the understanding of integrating character education values in the context of the rambu solo' ritual, by examining the role of traditional culture and the perspective of Christianity in Torajan society.